Report of a religious delegation to Spain, April 1937 - Macmurray, John, 1891-1976 ; Whately, Monica ; Beer, M. ; Iredell, E. O. ; Davies, D. R. (David Richard), 1889-1958 ; Ingram, Kenneth, 1882-1965 ; Levertoff, O. ; Laurie, Hannah; Johnson, Hewlett, 1874-1966 (London : V. Gollancz, 1937)
1937 SA14-049-010 36 p. ; 20 cm. 15X/2/566/196